Teacher Perceptions of the Application of Project-Based Learning Models to Improve Critical Thinking - Nurdianawati, Nita Dewi; Slamet, STY.; Indriayu, Mintasih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This article discusses teachers' perspectives on project-based learning to improve students' critical thinking skills. This project-based learning model can improve students' problem-solving thinking through project-based experience and students' direct understanding. In fact, this study contributes to the existing literature, refines the study model, and overcomes key challenges in its implementation. Indeed, this study aims to provide valuable insights into how project-based learning can be used to improve critical thinking skills in primary schools. From a professional perspective, it is hoped that this study can inspire and motivate teachers to implement project-based learning programs to improve students' critical thinking ability. A total of 53 participants agreed that the project-based learning model can improve students' critical thinking skills.